2004
DOI: 10.1021/ef049901+
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance and Ruthenium Ion Catalyzed Oxidation Reaction Analysis for Further Development of Aromatic Ring Size through the Heat Treatment of Coking Coals at >500 °C

Abstract: The development of aromatic cluster size in heat-treated coals by heating above 500 °C is discussed. Heat treatment of coal was performed at 500, 600, and 700 °C to obtain semicoke samples. The temperature range was above the resolidification temperature of the coal samples. For comparison, a strongly coking coal, Australian Goonyella coal, and a slightly coking coal, Chinese Enshu coal, were used as the sample coals. Analysis of the virgin coals and the semicoke samples with solid-state 13C NMR indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Followed by GC/MS identification of the released products, it has been first developed for the analysis of coals (Stock and Tse ; Stock and Wang ; Kidena et al. ) and then largely applied on other terrestrial samples like kerogens (Boucher et al. ; Standen et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Followed by GC/MS identification of the released products, it has been first developed for the analysis of coals (Stock and Tse ; Stock and Wang ; Kidena et al. ) and then largely applied on other terrestrial samples like kerogens (Boucher et al. ; Standen et al.…”
Section: Resultsmentioning
confidence: 99%
“…This mild oxidation results in the release of the acyclic and cyclic aliphatic substituents to which the aromatics are bound as acyclic and cyclic carboxylic acids, the carboxylic functional groups marking the attachment points on the aromatic moieties. Followed by GC/MS identification of the released products, it has been first developed for the analysis of coals (Stock and Tse 1983;Stock and Wang 1985;Kidena et al 2004) and then largely applied on other terrestrial samples like kerogens (Boucher et al 1990;Standen et al 1991;Kribii et al 2001;Li et al 2004), asphaltenes (Strausz et al 1999;Li et al 2010;Muhammad and Abbott 2013), crude oil (Warton et al 1999), soil IOM (Qu en ea et al 2005Winkler et al 2005), and nonhydrolyzable algal biopolymers (Blokker et al 2000(Blokker et al , 2006. Recently, this technique was also used in the analysis of carbonaceous meteorites (Remusat et al 2005b).…”
Section: Ruo 4 Oxidation Of the Iommentioning
confidence: 99%
“…The appearance of the metaplast material facilitated the movement and orientation adjustment of aromatic layers during pyrolysis; this resulted in the rapid stacking and condensation of aromatic layers. 5,6,[11][12][13][14] Then, the L a , L c , and N values of 1FeJXO15-800H, 3FeJXO15-800H, and 6FeJXO15-800H decreased, and the d 002 values increased; this indicated that the microcrystalline structure was transformed into a type of disordered structure during pyrolysis in the presence of FeCl 3 catalyst and oxygen functional groups. Compared to that of the oxidized char (JXO15-800) without the addition of the FeCl 3 catalyst reported in our previous study, 22 the degree of disorder in 1FeJXO15-800H, 3FeJXO15-800H, and 6FeJXO15-800H was further promoted by increasing the amount of FeCl 3 catalyst, and Fe might penetrate into an aromatic structure during pyrolysis to enlarge the aromatic structure layer distance (d 002 ).…”
Section: Crystal Structure Analysis Of Coal Chars Produced By Pyrolysismentioning
confidence: 99%
“…At rst, in the beginning of the activation process, a small amount of initial pores can hinder the diffusion of the activated gas into the particles' interior to produce more pores; this leads to the occurrence of more reactions on the particle surfaces. [11][12][13][14] Then, with an increase in the activation time, the highly ordered conversion of the carbon structure at high temperatures can reduce the number of active sites; this hinders the sustained growth of micropores inside the particles and continually increases the external loss of quality. 15 Therefore, the simultaneous resolution of the abovementioned two problems is the key to achieve a high S BET /burn-off value.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that it is difficult to obtain ideal AC production only by adjusting the activation condition; thus, the key factor is the improvement of the physicochemical structure of the coal char at the pyrolysis stage. More initial pores can rapidly promote the diffusion of the activated gas into the interior of the particles to avoid external loss of quality, and many active sites can promote the reaction between the activation agent and carbon matrix to produce more micropores and mesopores …”
Section: Introductionmentioning
confidence: 99%